Traffic and Warehouse Department of Monark Equipment Corporation - Dayday, Lourdes (College of Engineering, 1989)
This project study is on Industrial Systems Design; a study on systems: its design, performance, problems, improvements etc? The purpose of this study is to solve systems problems and improve systems performance. The subject of interest of this study is the Traffic and Warehouse Department. The present system, its problems, and its opportunities for improvement is studied using the systems approach; that is, the TWD is not viewed as an isolated system but rather, as a part of a larger system. Thus, in trying to improve the efficiency of TWD, consideration was given to its effects on the other systems to which it is interlinked and subordinated to. In essence, these are the steps undertaken in the conduct of the study: 1) Initial Survey of the Monark System followed by the Selection of the Subsystem to be studied; 2) Data Gathering and Validation; 3) Problem Diagnosis; 4) Further Data Gathering and Validation; 5) Problem Formulation; 6) Problem Solving and Search for Alternative Designs; and 7) Specification of Solution to Identified Problems and Specification of other Recommendations. These are the Findings and the Recommendations: 1) F: What makes order-filling or picking take long are those instances when items cannot be located in the location specified in the picking note. C: The identified controllable and significant causes are the cases of "unbinned arrivals" and "misplaced parts." R: a) Modify computer system such that inventory stock level is incremented not immediately upon arrival of shipment but 34 or 48 hours (for 20-footer and 40-footer respectively) upon release of binning list. b) The ongoing installation of new bins be expedited c) The planned labeling of bin opening with part numbers be implemented d) Manpower Training on Work Attitudes e) For the perpetual inventory inspections, assign weights to all the parts basing this weight on speed of movement and on the value of the part. The varying weights assigned vary the choices or probabilities of each part from being picked as sample. 2) F: Customer-waiting type and rush-type of picking notes are expected to be processed in TWD immediately, but often times this fails to happen/ C: Identified controllable causes are: 1) unnoticed PN in computer printer 2) PN's getting "lost" or hidden underneath a pile of less urgent PN's 3) FIFO sequence is not strictly followed R: a) Install a buzzer as an interface between counter sales and warehouse-on-the-floor. b) Instruct and Supervise warehouse personnel to put all incoming PN's beneath the existing pile, and process the orders from top to bottom. c) The leadman should consistently act as dispatcher of the PN's. d) Install a separate paper rack for customer-waiting type of PN's.